EFFECT OF PROGRESSIVE MUSCULAR RELAXATION ON ANXIETY LEVELS IN PATIENTS WITH CHRONIC KIDNEY DISEASE UNDERGOING HEMODIALYSIS IN THE GENERAL HOSPITAL OF TUGUREJO SEMARANG, INDONESIA - Ary Astuti; Anggorowati Anggorowati; Andrew Johan (Belitung Raya Foundation, Indonesia, 2017)
Background: Patients with chronic kidney disease undergoing hemodialysis suffer changes in lifestyle, which cause physical and psychosocial problems, particularly anxiety. Progressive muscular relaxation is considered as an intervention to reduce anxiety. Objective: This study aims to examine the effect of progressive muscular relaxation in in reducing anxiety in patients with chronic kidney disease undergoing hemodialysis. Methods: This study used a quasi-experimental design involved 78 respondents, with 38 randomly assigned in the intervention and control group. The progressive muscular relaxation was performed on 14 muscle groups for 4-week period. Hamilton anxiety rating scale was used to measure anxiety. Univariate, bivariate and multivariate analyses were performed for data analyses. Results: The results showed a statistically significant difference in anxiety values between the intervention and control group with p-value 0.000 (<0.05). Conclusion: There was a significant effect of progressive muscular relaxation in reducing anxiety in patients with chronic kidney disease undergoing hemodialysis. The results of this study is expected to be one reference in making the progressive muscular relaxation as a nursing intervention in reducing anxiety in patients undergoing hemodialysis.